PERANCANGAN INFRASTRUKTUR DEVOPS SISTEM INFORMASI SENTRA HKI LPPM UNSOED - Daniswara Sutarman, Muhammad; Fadli, Ari; Syaiful Aliim, Muhammad (Universitas Tarumanagara, 2023)
Intellectual Property Rights are rights that arise from the results of thought processes that produce a product or process that is useful for humans. Objects regulated in IPR are works born out of human intellectual abilities. Management Information System is a planning system part of the internal control of a business which includes the use of people, documents, technology, and procedures by management accounting to solve business problems such as the cost of products, services, or a business strategy. LPPM Unsoed HKI Center as an institution tasked with managing and maintaining IPR documents collected from various organizations and individuals. This study aims to design and implement infrastructure using the DevOps method for information system development. In this method, several tools are used to build information systems, namely Linux Ubuntu 20.04, Github, Jenkins, Docker and Apache Web Server. Jenkins is a tool used to ensure continuous integration. Github as a tool to ensure continuous development and continuous integration. While docker as part to support continuous deployment. This research has several stages in the process, namely plan, code, build, test, release, deploy. The result of this research is the Unsoed Intellectual Property Rights Information System which has been successfully implemented using the DevOps method